PENGARUH LITERASI KEUANGAN DAN KONFORMITAS TEMAN SEBAYA TERHADAP PERILAKU KONSUMTIF DI KALANGAN REMAJA - Virna Indri Cahyani; Ati Sadiah; Kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2024)
The problem in this study is how the description of consumptive behavior in Siliwangi University students who come from the JABODETABEK area. This study aims to determine the effect of financial literacy and peer conformity on student consumptive behavior. The method used in this research is survey. The population in this study was 335. The sampling technique used in this study was simple random sampling so that the sample obtained was 182 students. The data collection technique used is a questionnaire distributed via google form with multiple linear regression analysis techniques. The results showed that financial literacy had no significant effect on student consumptive behavior, while peer conformity partially had a significant effect on consumptive behavior. Then, simultaneously the two variables have a significant effect on the consumptive behavior of students.